Environmental impacts of hydropower plants in Brazil: an identification guide (Sustainability in Debate, 2022)
This paper presents a guide for identifying the environmental impacts of hydroelectric enterprises. The qualitative research used the following methods: case studies, systematic literature review (SLR), content analysis, and consultation with expe ts. Four sources of information were used, including Environmental Impact Statements (EISs), scientific articles, best practice guides, and expert consultation. All EISs of hydroelectric plants submitted to the Brazilian federal Environmental Licensing between 2010 and 2020 (8 EISs) were analysed. RSL identified 68 scientific papers eligible for analysis and collection of impacts. The results were compared with Canadian practice and discussed in a virtual workshop of 15 expe ts. The guide has 90 impacts and can be used by environmental consulting firms and environmental agencies in the preliminary identification of environmental impacts of hydroelectric dams, contributing to the improvement of planning carried out in the EIA scoping stage of future environmental studies of this type.